The Important Meaning of the Archives of the Indonesian Sugar Plantation Research Center for the Period 1893-1982 in the Collective Memory of the Nation and UNESCO - Suwardi, Tiat S.; Rokayah, Siti; Atmodjo, Susilo Dwi; Faqih, M. Ubaidillah (Program Studi Ilmu Perpustakaan UIN Alauddin, 2026)
Background: The archives of the Indonesian Sugar Research Center (P3GI), spanning 1893 to 1982, represent more than technical records; they are a vital repository of the nation’s colonial and postcolonial industrial identity. Within the framework of Jan Assmann’s Cultural Memory, these archives serve as a cornerstone for shaping Indonesia’s collective historical consciousness. Purpose: This study argues for the recognition of the P3GI archives as significant national documentary heritage. It examines their historical, symbolic, and institutional value in recording the complex interplay between science, technology, power, and the socio-economic dynamics of the Indonesian sugar industry. Methods: Utilizing a qualitative exploratory approach, the researchers conducted semi-structured interviews with six key informants, supplemented by an extensive review of P3GI documents and archival policies. Data were analyzed using content analysis mapped against Assmann’s five dimensions of cultural memory: content, form, media, time structure, and participation structure. Findings: The results show that the P3GI archives meet all of the requirements for cultural memory. Beyond being mere data sources, they function as an infrastructure for collective memory, documenting the evolution of the sugar industry through various political eras. Furthermore, the digitization of these records and their registration as Memoria Mundi Bangsa (MKB) highlights the role of multi-actor collaboration in legitimizing and transmitting memory across generations. Originality/Value: These findings reinforce the strategic position of the P3GI archives as a national documentary heritage and support the development of archive preservation policies based on cultural and historical values.